Christian Gottlob Proft og de utilladelige skrifter. Bogforbud i årene efter trykkefrihedsperioden - Jakobsen, Jesper (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
In 1770 Christian VII’s personal physician Johann Friedrich Struensee exploited the king’s feeble condition to seize power in Denmark and one of his first acts was to introduce unrestricted freedom of the press. Two years later in January 1772, Struensee was himself toppled from power and subsequently executed in April of the same year. It was soon clear that the new regime aimed to reintroduce a form of control over book publication and the present article how these new restrictions were viewed from the perspective of the Copenhagen bookseller Christian Gottlob Proft (1736–1793). In the years 1773–76 Proft twice found himself the object of the authorities’ suspicions, as he had distributed printed matter which the authorities regarded as impermissible. In 1773, Proft was convicted of having provided the itinerant bookseller Hermann Ludolph Bardewyck with forbidden writings which the new rulers regarded as dangerous as they espoused Struensee’s cause and potentially could undermine the legitimacy of the new rulers. Three years later, Proft announced that he intended to publish Johann Wolfgang von Goethe’s novel Die Leiden des jungen Werthers in a Danish translation, but its publication was blocked for religious and moral reasons. These two court cases brought against Proft show that, even though the abolished censorship was not reintroduced, actual practice had changed very little. The abolished law of censorship was still applied in legal judgements, just as the government made no bones about banning the translation of a work it did not wish to see circulated among the common people. Further, they resorted to the well-tried method of inflicting severe sentences on representatives of the book trade rather than carrying out comprehensive control of the authors.